2021
DOI: 10.3390/buildings11110553
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Gender Issues in the Australian Construction Industry through the Lens of Empowerment

Abstract: Gender equality at work in male-dominated industries is conditioned by intrinsic systemic issues which established policies have, to a significant extent, failed to address, as women’s participation remains under-represented. This study argues for the reappraisal of the issue through a different lens and carries out a systematic and thematic review of the literature on women in construction in Australia through a women’s empowerment framework. Despite its usual application in gender inequality at work in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…These four domains are cognitive, interpersonal, business, and strategic. The methodological approach is illustrated in Figure 1 [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four domains are cognitive, interpersonal, business, and strategic. The methodological approach is illustrated in Figure 1 [39].…”
Section: Methodsmentioning
confidence: 99%
“…These four domains are cognitive, interpersonal, business, and strategic. The methodological approach is illustrated in Figure 1 [39]. The first step of this study is to define the searching keywords and the searching database.…”
Section: Methodsmentioning
confidence: 99%
“…An effective intervention to avoid unplanned additional costs would be to allocate gender-inclusive facilities budgets at the initial stage of the project (Regis et al, 2019). Differences in the physical capabilities of men and women relating to strength can be reduced through the introduction of new technologies and equipment (Wang et al, 2021).…”
Section: Allocating Gender-equality Facilities and Equipment Budgetsmentioning
confidence: 99%
“…In addition to increasing overall job satisfaction, self-esteem workshops provide the opportunity for women to learn to manage conflicts and become less sensitive to discrimination, and male dominance, in male-dominated work environments (Wang et al, 2021). Training programmes (such as programme to promote women's employment) are proven to increase female participation in male-dominated sectors (Peñalvo-López and Cárcel-Carrasco, 2019).…”
Section: Training Programme and Workhopsmentioning
confidence: 99%
“…The current study revealed that the most frequently researched diversity factors in the CS are gender, race, ethnicity, and culture. The majority of the articles focused on issues such as women in the CS [58,65,66], gender stereotyping [67,68], discrimination against women [69] and ethnic minorities [70,71], and cultural diversities and communication problems [29,72] among migrant workers. A limited number of studies have also been carried out on the sexual orientation of employees in the industry [73][74][75].…”
Section: Research Gap and Future Directionsmentioning
confidence: 99%